ANALISIS KUALITAS LAYANAN WEBSITE E-COMMERCE TERHADAP KEPUASAN PENGGUNA MENGGUNAKAN METODE WEBQUAL 4.0 - Himawat Aryadita; Dyah Ayu Widyastuti; Niken Hendrakusuma Wardani (UIN Syarif Hidayatullah Jakarta, 2017)
Along with the increasing development of e-commerce in Indonesia, the increase number of complaints to Indonesian Consumers Organization (YLKI) received 1192 cases in 2014 and 1030 cases in 2015. Online shop category becomes one of the major problem faced by the consumers considering online shop belongs to top 10 complaints received by YLKI. This study examines the extent to which the user satisfaction in using e-commerce website. The websites which were examined in this study are Bukalapak, Tokopedia and Lazada. The study conducted by using WebQual 4.0 method with 347 respondents. The analysis shows that Bukalapak websites is considered as the better website on all categories. Based on respondents’ assessments, the value of WQI on Bukalapak website is on the category of Usability (0.70), Information Quality (0.70) and Service Interaction (0.65). The most important factor toward user satisfaction is the usability to user satisfaction.